If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(3x + -6) = 26 Reorder the terms: 8x + -1(-6 + 3x) = 26 8x + (-6 * -1 + 3x * -1) = 26 8x + (6 + -3x) = 26 Reorder the terms: 6 + 8x + -3x = 26 Combine like terms: 8x + -3x = 5x 6 + 5x = 26 Solving 6 + 5x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5x = 26 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 26 + -6 5x = 26 + -6 Combine like terms: 26 + -6 = 20 5x = 20 Divide each side by '5'. x = 4 Simplifying x = 4
| 7(2x-1)=11x+5 | | 2a+7=-2-3 | | H=68t-8t | | (9(y+5)-18)+(3(y-3)+5)= | | 5=7-7x | | p^2+4p+4=40 | | 2x-(x+1)= | | (8y-5)6y-7= | | 4(x+5)5=2x-4 | | 6d-11/2=2d-13/2 | | (X+10)2=y+100 | | 24x+19x=180 | | 7/10x=14/5 | | 17-x=172 | | 70-61x+4x^2=0 | | -3=-6-x | | -24+5x+x^2=0 | | x^3+3x^2-15x=0 | | -24+x^2=0 | | -9(x+9)+4=-77 | | 18000=p(1+.12*2) | | 21y=4(5x-6) | | 7(4s+1)=63 | | 70-16x+4x^2=0 | | 2b=20-28 | | 5c+15=15+4c-2 | | 5+x-4=14 | | 7x+4-2x=5x+4 | | (e^5x+3)-8=0 | | n-45+25-9= | | 2x+6x=-5+7 | | y=.0388ln(x)+.0366 |